2010
DOI: 10.2134/jeq2010.0041
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Source Effects on Nitrous Oxide Emissions from Irrigated No‐Till Corn

Abstract: Nitrogen fertilization is essential for optimizing crop yields; however, it may potentially increase nitrous oxide (N2O) emissions. The study objective was to assess the ability of commercially available enhanced-efficiency N fertilizers to reduce N2O emissions following their application in comparison with conventional dry granular urea and liquid urea-ammonium nitrate (UAN) fertilizers in an irrigated no-till (NT) corn (Zea mays L.) production system. Four enhanced-efficiency fertilizers were evaluated: two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
88
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 20 publications
18
88
6
1
Order By: Relevance
“…Few studies have reported EI. The values in the current study are about one order of magnitude greater than reported for irrigated corn (0.03-0.07 kg N 2 O-N Mg -1 ) in Colorado by Halvorson et al (2010b) and conventional and no-till corn (0.05-0.10 kg N 2 O-N Mg -1 ) in Minnesota by Venterea et al (2011). Our EI values were less than reported for more humid climes with winter wheat (1.0-2.5 kg N 2 O-N Mg -1 ) receiving combinations of urea and farmyard manure in Shaanxi Province, China (Wei et al, 2010) and corn (1.3-2.0 kg N 2 O-N Mg -1 ) receiving urea-NH 4 NO 3 , calcium ammonium nitrate, and aqueous NH 3 in Quebec (Gagnon et al, 2011).…”
Section: Applied Nitrogen and Yield Scaled Nitrous Oxide Emissionscontrasting
confidence: 68%
See 2 more Smart Citations
“…Few studies have reported EI. The values in the current study are about one order of magnitude greater than reported for irrigated corn (0.03-0.07 kg N 2 O-N Mg -1 ) in Colorado by Halvorson et al (2010b) and conventional and no-till corn (0.05-0.10 kg N 2 O-N Mg -1 ) in Minnesota by Venterea et al (2011). Our EI values were less than reported for more humid climes with winter wheat (1.0-2.5 kg N 2 O-N Mg -1 ) receiving combinations of urea and farmyard manure in Shaanxi Province, China (Wei et al, 2010) and corn (1.3-2.0 kg N 2 O-N Mg -1 ) receiving urea-NH 4 NO 3 , calcium ammonium nitrate, and aqueous NH 3 in Quebec (Gagnon et al, 2011).…”
Section: Applied Nitrogen and Yield Scaled Nitrous Oxide Emissionscontrasting
confidence: 68%
“…The EFs were greater than those observed for surface placement with irrigated corn in Colorado, which ranged from 0.003 to 0.008, 0.002 to 0.004, and 0.001 to 0.003 kg N 2 O-N kg -1 N for urea, ESN, and SuperU, respectively (Halvorson et al, 2010b(Halvorson et al, , 2011. Only a conventionally tilled, continuous corn system had EFs similar to the current study, at 0.009 and 0.008 kg N 2 O-N kg -1 N for urea and ESN, but notill continuous corn and corn-dry bean (Phaseolus vulgaris L.) and corn-barley rotations were less (<0.004 kg N 2 O-N kg -1 N) (Halvorson et al, 2010a).…”
Section: Applied Nitrogen and Yield Scaled Nitrous Oxide Emissionsmentioning
confidence: 58%
See 1 more Smart Citation
“…With higher crop biomass (i.e., due to good growing conditions), it is likely that plant-respired CO 2 levels overwhelmed the quantity of CO 2 emitted from soil, and thereby reduced the magnitude of the impact of N fertilization on CO 2 emissions. This may partly explain why N fertilization often has no impact under warmer climates such as found in the US corn belt (Halvorson et al 2010;Venterea et al 2010;Sistani et al 2011;Halvorson and Del Grosso 2012). This increased contribution of plantderived CO 2 to total soil respiration could be the result of a greater autotrophic respiration and (or) of a lower soil N concentration due to greater N uptake.…”
Section: Soil Respiration Vs N Source and Rate Under Field Conditionsmentioning
confidence: 99%
“…For their part, Ding et al (2007) reported an 18% decrease using urea during the corn elongation stage. Applying either other different sources of N (anhydrous NH 3 , liquid urea ammonium nitrate (UAN), or ammonium nitrate) was found to have little impact on CO 2 emissions (Halvorson et al 2010;Venterea et al 2010;Sistani et al 2011;Halvorson and Del Grosso 2012), whereas by contrast certain studies observed a decrease in CO 2 emissions with ammonium nitrate Wilson and Al-Kaisi 2008). In a 45 d incubation, Ramirez et al (2010) reported that N fertilizer addition under different forms (NH 4 NO 3 , KNO 3 , NH 4 Cl, (NH 4 ) 2 SO 4 and Ca(NO 3 ) 2 ) all decreased microbial CO 2 production.…”
Section: Introductionmentioning
confidence: 99%